The Effect of Company Ownership Structure on Profit Information with Earnings Opacity as An Intervening Variable - Kurniasih Dwi Astuti; Hesti Fatmawati; Windu Mulyasari; Rudi Zulfikar (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to determine the effect of Company Ownership Structure on Profit Informative with Earnings Opacity as an intervening variable. The company's ownership structure is measured by looking at the percentage of ownership of the controlling shareholders with ownership above 50%. Earnings informativeness is measured by earnings response coefficient (ERC). Meanwhile, earnings opacity is proxied by earnings smoothing as measured using the Eckel index. The research population includes manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample selection method used was purposive sampling and 27 companies were selected with a total sample of 135 research data. The analysis technique used is multiple linear regression with SPSS version 25 software and path analysis with the help of an online sobel calculator. The results of this study indicate that the disclosure of Company Ownership Structure has a direct and significant negative effect on Profit Informativeness. Earnings opacity does not act as a mediator between the influence of Company Ownership Structure on Profit Informativeness.